Factors associated with undernourishment among people 20 years old or over with HIV/AIDS, attending public health services in the São Paulo municipality, Brazil - Katia Cristina Bassichetto; Denise Pimentel Bergamaschi; Vania Regina Salles Garcia; Maria Amélia de Sousa Mascena Veras (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The study evaluated the nutritional status of 629 people living with HIV/AIDS attended at 12 specialized services of São Paulo's Municipal Health Department, Brazil. Data were obtained from medical records and through interviews during nutritional consultation. We used the classification criteria established by World Health Organization to assess malnourished individuals, a BMI < 18.5kg/m2. The prevalence of malnutrition in people with AIDS is 3.12 times that observed among people with HIV, and among people with co-infection it is 3.41 times that obtained among people without co-infection. This indicates how these conditions can harm the maintenance of the nutritional status, and shows that they demand a comprehensive understanding of the mechanisms involved in this phenomenon, as well as the development of strategies to improve the health care of individuals at nutritional risk.